Earnings Announcements and Stock Price Behaviour: An Event Study on the Efficiency of India’s Stock Market - Sharma, Pranav (2013)
The aim of this dissertation is to use event study methodology to analyse both the information content of accounting earnings and the speed at which stock prices adjust to new information in an emerging market such as India’s, where accounting standard are not yet in line with that of International Financial Reporting Standards. The sample is composed of 665 earnings announcements (events) of firms constituting the S&P BSE 500 index during the fiscal years 2007-2012. Depending on the surprise component of earnings announcements, the events are grouped into three information categories: good news, bad news or no news. Consensus analyst forecasts are used as a proxy for expected earnings in order to determine the surprise component, and abnormal returns are estimated using the market model for normal returns. Several key results are revealed. Firstly, investors react positively to good news and negatively to bad news, as is expected. Secondly, India’s stock market is relatively efficient in response to good earnings news, but there is evidence of a negative post-earnings announcement drift for over a week when there is bad earnings news, which rejects the efficient market hypothesis. Finally, the inefficiency is particularly evident in the bull market of 2009 and 2010. In terms of study limitations, the non-normality of abnormal returns in the bad news category is concerning since parametric tests are use, and so generalised sign and rank non-parametric tests appear to be favourable alternatives.